Human Resource Management in Preventing Turnover Intention at Syubbanul Wathon 2 Bandongan Middle School - Dwi Fitria Nur Azizah; Ahmad Fuad Hasyim; Muhammad Sholikhun (CV. Creative Tugu Pena, 2024)
Human resources are an important asset and act as the main driving factor in the implementation of all agency activities, so they need to be managed well through human resource management. Human resource management needs to be implemented in educational institutions as a form of effort to improve the quality of education, especially in the field of teaching staff and education. This research aims to explore human resource management (HR) in preventing turnover intention among Government Employees with Employment Agreements (PPPK). This research uses a descriptive method with a qualitative approach. The research uses primary and secondary data through interviews, observation and documentation as data collection instruments. The results of the research suggest that human resource management can prevent turnover intention at Syubbanul Wathon Bandongan Middle School, namely with 3 policies. This policy has positive synergies as a solution to the PPPK impact. This includes teacher transfer deadline policies, issuance of work agreements, and assessments for teacher empowerment.